La pertinencia de la historia en la enseñanza de ciencias: argumentos y contraargumentos - Lombardi, O. I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
Adding up to the debate about the possibility of a historical view in science teaching, the present article frames some responses to the criticisms that, on the basis of the need of simplification and reconstruction of history , object its intrusion in science education. In that sense, the essentially constructive character of history and, particularly, of history of science is appointed, where the epistemological position of the historian acquires special relevance. The multiplicity of historical stories is a constituent characteristic of history and, thus, it does not represent an obstacle in sciences teaching.